2013
DOI: 10.1038/jid.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Rac Activation Is Not Sufficient to Initiate Melanocyte Neoplasia but Accelerates Malignant Progression

Abstract: Deregulated Ras signaling initiates and maintains melanocyte neoplasia. The Rho-like GTPase Rac has been implicated in Ras-induced neoplastic transformation. Moreover, a recurrent UV-induced mutation activating RAC1 has recently been detected in human melanoma. Here, a role for Rac in melanoma initiation and progression was investigated in human melanomas and zebrafish models of melanocyte neoplasia. Immunohistochemical analysis revealed RAC expression and activity restricted to melanocytes at the junction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Interestingly, we were able to detect not only strong upregulation of ERK but also activation of the small GTPase Rac1 in its active form as Rac1-GTP (18,19) in both secondary malignant melanomas and keratinocytic tumours. In melanoma with mutant BRAF, ERK as an effector of the MAPK pathway (15,20,21), and Rac1 is known to be constitutively activated in dysplastic naevi, primary melanomas, and melanoma metastases but absent from adjunct benign naevi (16)(17)(18)(19)22) and overexpressed in squamous cell carcinoma (23). Rac1 plays an important pathogenetic role in melanoma, as it is not only constitutively activated when mutated (Rac1 P29S ) in approximately 9.2% of sun-exposed melanomas (17) but also leads to increased cycling of melanoma cells (20,21).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, we were able to detect not only strong upregulation of ERK but also activation of the small GTPase Rac1 in its active form as Rac1-GTP (18,19) in both secondary malignant melanomas and keratinocytic tumours. In melanoma with mutant BRAF, ERK as an effector of the MAPK pathway (15,20,21), and Rac1 is known to be constitutively activated in dysplastic naevi, primary melanomas, and melanoma metastases but absent from adjunct benign naevi (16)(17)(18)(19)22) and overexpressed in squamous cell carcinoma (23). Rac1 plays an important pathogenetic role in melanoma, as it is not only constitutively activated when mutated (Rac1 P29S ) in approximately 9.2% of sun-exposed melanomas (17) but also leads to increased cycling of melanoma cells (20,21).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that the Rac1 V12 mutation, which induces a constitutive activation of Rac1, leads to anchorageindependent growth in soft agar and is able to induce tumors in vivo upon transplantation in immunocompromised mice [45], suggesting that V12Rac1 can act as an oncogene. However, the expression of constitutively active RAC1 V12 in zebrafish in vivo is neither sufficient to induce melanoma formation alone, nor cooperates with BRAF V600E , but accelerates HRAS V12 -induced melanoma nodule formation in vivo [46]. It is somewhat puzzling that RAC1 V12 is not sufficient to induce melanoma formation in zebrafish in vivo, whereas the RAC1 P29S mutation leads to increased proliferation and migration of cultured melanocytes [42[black small square],46].…”
Section: Common Gene Network Link Melanoma With Embryonic Neural Crementioning
confidence: 99%
“…HTB-72), and MNT-1 (a gift from Dr. P. G. Natali (University La Sapienza, Rome, Italy)) were grown in RPMI 1640 complete medium as described (22). Originally, the MJS line was indicated as representative of a very early stage of tumor differentiation (24) and by others as a VGP phenotype (25). SK28 line has been raised from a tumor that recurred after 4 years from the original tumor (26) and is indicated by others as metastatic (20,27).…”
Section: Methodsmentioning
confidence: 99%